COMPUTER ERGONOMICS DAN REPETITIVE STRAIN INJURY PADA PEGAWAI UNIVERSITAS SELAMA PANDEMI - Rouna Paoki; Grace Fresania Kaparang (NUTRIX, 2022)
Abstract The "new normal" conditions due to the COVID-19 pandemic have forced all to work from home and many people are just lacking of the knowledge to organize an ergonomic workplace thus, opening the potential to produce new problems, one of which is repetitive strain injury. This study aims to investigate the description of computer ergonomics behavior and repetitive strain injury figures in employees of K university, Indonesia. With a descriptive method and a cross-sectional approach, a simple random sampling technique, this study was attended by a total of 78 people but only 65 participants filled in the data completely. RULA score and Nordic Body Pain are used as research instruments. The results showed that risky computer ergonomics behavior of the majority of employees (n=64; 98.5%) universities resulting in repetitive strain injury in the majority (n=70; 89.7%) of participants, with complaints of neck pain (n=54; 69.23%), right shoulder pain (n=33; 42.3%) and left shoulder pain (n=24; 30.7%) as the three most painful sites. Recommendations for university administrators to hold computer ergonomics training to their employees, and for subsequent research to continue research with an experimental approach to the handling of emerging RSI. Keywords: computer ergonomics, pandemic, repetitive strain injury, university employee Abstrak Kondisi “new normal” karena pandemi COVID-19 ini memaksa semua untuk bekerja dari rumah dan banyak orang yang minim dalam pengetahuan untuk mengatur tempat kerja yang ergonomis sehingga berpotensi menghasilkan masalah baru yang salah satunya adalah repetitive strain injury. Studi ini bertujuan melihat gambaran perilaku computer ergonomics dan angka repetitive strain injury pada pegawai universitas K, Indonesia. Dengan metode deskriptif dan pendekatan potong lintang, teknik pengambilan sampel simple random, penelitian ini diikuti oleh total 78 orang namun hanya 65 partisipan yang mengisi data dengan lengkap. RULA score dan Nordic Body Pain digunakan sebagai instrumen penelitian. Hasil penelitian menunjukkan perilaku computer ergonomics yang berisiko dari mayoritas pegawai (n=64; 98.5%) universitas sehingga mengakibatkan repetitive strain injury pada mayoritas (n=70; 89.7%) partisipan, dengan keluhan nyeri leher (n=54; 69.23%), nyeri bahu kanan (n=33; 42.3%) dan nyeri bahu kiri (n=24; 30.7%) sebagai tiga tempat terbanyak yang nyeri. Rekomendasi bagi administrator universitas untuk dapat memberikan pelatihan computer ergonomics pada pegawainya, dan untuk penelitian selanjutnya untuk dapat melanjutkan penelitian dengan pendekatan eksperimental untuk penanganan RSI yang muncul. Kata Kunci: computer ergonomics, pandemi, pegawai universitas, repetitive strain injury